Comparação entre histologia e espectroscopia de fluorescência para avaliação de atrofia cutânea induzida por glicocorticóide em ratos - Lemos, Moyses Costa (Universidade Federal de São Carlos, 2010)
The gold standard for evaluating skin atrophy is the histological study. When compared to the technique of Fluorescence Spectroscopy (FS), histology requires the physical removal of tissue and their processing in the laboratory, while the FS conducts fast assessments in vivo. The objective of this study was to standardize a methodology for inducing skin atrophy in an experimental model, compare the collagen in normal and atrophic skin, and estimate the potential assessment of FS in skin atrophy. We used 20 adult male Wistar rats, from the UFSCar Central Animal Biotery, kept in a controlled environment. The cutaneous atrophy was induced with topical use of the glucocorticoid Clobetasol propionate 0.05%, 2 times daily for 14 days and evaluated by histological analysis and FS with laser excitation at 532nm and 408nm. We evaluated 96 skin fragments with HE and picrosirius red staining. In biopsies from the first day, the average of epidermal thickness was 44 ± 9μm and, after 14 days of CB, was 16 ± 6μm (p <0.0001), confirming atrophy. This result was confirmed by staining with picrosirius red, which was observed coarsed and disorganized rearrangement of the collagen fibers in the dermis after the use of corticosteroids. For the analysis of results from FS, the spectra have been nominated as "normal" or "atrophic" in correspondence to the histological study. The FS with 408nm laser analysis allowed to distinguish the "normal" and "atrophic" group with fewer spectral parameters. In the future, this technique could be used as a complementary diagnostic method in dermatology.
Keywords: Biotecnologia; Histologia (Tecido); Espectroscopia de fluorescência; Medições com laser; Dermatologia; Atrofia cutânea; Glicocorticóide; Histologia; Laser; Dermal atrophy; Glucocorticoid; Histology; Fluorescence spectroscopy; Laser; Dermatology; OUTROS